Association of tumor necrosis factor-alpha promoter region gene polymorphism at positions -308G/A, -857C/T, and -863C/A with etanercept response in Iraqi rheumatoid arthritis patients - Samer Mohammed; Munaf Zalzala; Faiq Gorial (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate the association between polymorphisms in the promoter region of the tumor necrosis factor-alpha (TNF-α) gene at locations -308G/A, -857C/T, and -863C/A with the tendency of being non-responder to etanercept. Patients and methods: Between October 2020 and August 2021, a total of 80 patients (10 males, 70 females; mean age: 50 years; range, 30 to 72 years) with rheumatoid arthritis (RA) receiving etanercept for at least six months were included. The patients were divided into two groups responders and non-responders, based on their response after six months of continuous treatment. Following polymerase chain reaction amplification of the extracted deoxyribonucleic acid, sequencing by Sanger method was performed to identify the polymorphism at the TNF-α promoter region. Results: In the responder group, the GG genotype of (-308G/A) and the AA genotype of (-863C/A) were both significantly present. The CC genotype of (-863C/A) was significantly present in the non-responders group. The CC of (-863C/A) SNP was the only genotype that appeared to increase the likelihood of being resistant to etanercept. The GG genotype of (-308G/A) was negatively correlated with the likelihood of being a non-responder. The (-857CC) and (-863CC) genotypes were significantly more prevalent in the non-responders group. Conclusion: The presence of the (-863CC) genotype, alone or in combination with (-857CC), is linked to an increased likelihood of becoming a non-responder to etanercept. The GG genotype of -308G/A and the AA genotype of -863C/A significantly increase the likelihood of becoming responder to etanercept.